Detection of high heteroplasmy in complete loggerhead and hawksbill sea turtles mitochondrial genomes using RNAseq (2021)
Sea turtle populations around the world face rapid decline due to the effect of anthropogenic and environmental factors. Among the affected populations are those of hawksbill turtles (Eretmochelys imbricata) and loggerhead turtles (Caretta caretta), which is why a greater effort is currently being made in their monitoring and tracing. The intragenic degree of heteroplasmic mutations, commonly associated with diseases of variable symptoms, has not been analyzed in these species. In this study, heteroplasmy in the complete mitogenome (mtDNA) of three loggerhead turtles and one hawksbill turtle was identified from data obtained by RNAseq. Individuals Cc3, Ei1, Cc1 and Cc2 presented 0.3, 1.7, 1.8 and 7.1% of heteroplasmic mutations in all their mtDNA, respectively. The protein-coding genes that presented the highest percentage of heteroplasmy were ND4 and ND5 in individual Cc2 with 16 and 38.6%, respectively. Of the tRNA genes, only tRNATyr was heteroplasmic in the four individuals with 5.63% (Cc1), 25.35% (Ei1 and Cc2) and 49.3% (Cc3). In this study, we identified the critical sites of heteroplasmy in each individual and the genetic variability of their mitogenomes. The data obtained represents the baseline for future projects that evaluate the population status of these species.